UWB Transmission through Human Thorax: An Index of Cardiac Health - Sahu, Kedar Nath; Naidu, Challa Dhanunjaya; Kottareddygari, Jaya Sankar (International Journal of Online and Biomedical Engineering (iJOE), 2020)
There are many applications which require remote and non-invasive measurement of heartbeat of a human being using an ultra-wideband (UWB) radar. Sophisticated models and their analysis need to be referred before the design of a practical radar prototype. In this paper, i) a UWB wave propagation model of human thorax and ii) the power transmission coefficients estimated from the simulations of the model in the range 1-10 GHz using MATLAB are presented. The study reveals that there is a periodic variation of the transmission coefficients in correlation with the instantaneous physical dimensions of an active heart.